2015
DOI: 10.1007/s00122-015-2645-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel Phakopsora pachyrhizi resistance allele (Rpp) contributed by PI 567068A

Abstract: The Rpp6 locus of PI 567102B was mapped from 5,953,237 to 5,998,461 bp (chromosome 18); and a novel allele at the Rpp6 locus or tightly linked gene Rpp[PI567068A] of PI 567068A was mapped from 5,998,461 to 6,160,481 bp. Soybean rust (SBR), caused by the obligate, fungal pathogen Phakopsora pachyrhizi is an economic threat to soybean production, especially in the Americas. Host plant resistance is an important management strategy for SBR. The most recently described resistance to P. pachyrhizi (Rpp) gene is Rpp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Thirteen of the 25 assays (11 near Rpp1 and two near the Rpp3 locus) detected polymorphisms between UG‐5 and 'Williams 82' (Table S1). The master mix and PCR cycling conditions used for the KASP assays were the same as those previously described by King et al (2016a). Endpoint readings were determined using a Roche LightCycler 480 II with LightCycler ® Software 2.0 (Roche Diagnostics Corporation Indianapolis).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen of the 25 assays (11 near Rpp1 and two near the Rpp3 locus) detected polymorphisms between UG‐5 and 'Williams 82' (Table S1). The master mix and PCR cycling conditions used for the KASP assays were the same as those previously described by King et al (2016a). Endpoint readings were determined using a Roche LightCycler 480 II with LightCycler ® Software 2.0 (Roche Diagnostics Corporation Indianapolis).…”
Section: Methodsmentioning
confidence: 99%
“…The Rpp1 , Rpp4 and Rpp6 loci are located on chromosome (Chr.) 18 (Chakraborty et al, 2009; Garcia et al, 2008; Hossain et al, 2015; Hyten et al, 2007; King et al, 2016a; Li et al, 2012). The Rpp2 gene was mapped to Chr.…”
Section: Introductionmentioning
confidence: 99%
“…Searching for resistant genotypes, the United States formalized a trademark for the Rpp5 gene selection, which promotes resistance to Asian rust (King et al, 2016). The method facilitates the development of resistant varieties to this pest.…”
Section: Inox ®mentioning
confidence: 99%
“…Multiple alleles of Rpp genes exist in soybean genomes, which show differential responses to selected P. pachyrhizi pathotypes or demonstrate different gene actions [56,62,71,77,82]. For instance, Chakraborty et al, [62] showed that a P. pachyrhizi isolate from Zimbabwe (ZM01-1) produced RB lesions on soybean line PI 594538A, but TAN lesions on PI 200492, the original source of Rpp1.…”
Section: Genetics Of Resistance To Sbr Resistancementioning
confidence: 99%